2023
DOI: 10.1088/2053-1591/ad0c7d
|View full text |Cite
|
Sign up to set email alerts
|

Integration of FDM and self-healing technology: evaluation of crack sealing by durability and mechanical strength

Noor A Hameed,
Farhad M Othman,
Alaa A Abdul-Hamead

Abstract: The tensile zone of concrete is prone to cracking due to its limited ability to withstand tension. To address this issue, steel reinforcement is used in these specific regions. The occurrence of little cracks might potentially facilitate the ingress of liquids and gases into the reinforcing material, hence inducing corrosion. Self-healing concrete can repair and seal minuscule cracks, thus impeding the formation of corrosion. This study investigates the potential application of fused deposition modelling (FDM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Analyzing the results regarding the control group showed that MC was an effective therapeutic drug, which is in line with other studies. Function as starting and promoting points for producing calcium-silicate-hydrate (C-S-H) compounds [42,43]. The threedimensional structure of the vascular system shows a greater ability to block a greater region of the fracture than the onedimensional (1D) and two-dimensional (2D) systems.…”
Section: Flexural Strength Recoverymentioning
confidence: 99%
“…Analyzing the results regarding the control group showed that MC was an effective therapeutic drug, which is in line with other studies. Function as starting and promoting points for producing calcium-silicate-hydrate (C-S-H) compounds [42,43]. The threedimensional structure of the vascular system shows a greater ability to block a greater region of the fracture than the onedimensional (1D) and two-dimensional (2D) systems.…”
Section: Flexural Strength Recoverymentioning
confidence: 99%